Preoperative localisation techniques in breast conservative surgery: A systematic review and meta-analysis. (December 2020) - Moreira, Inês C.; Ventura, Sandra Rua; Ramos, Isabel; Fougo, José Luís; Rodrigues, Pedro Pereira
Abstract: The preoperative localisation of non-palpable lesions guided by breast imaging is an important and required procedure for breast-conserving surgery. We conducted a systematic review and meta-analysis of the literature on the comparative impact of different techniques for guided surgical excision of non-palpable breast lesions from reports of clinical or patient-reported outcomes and costs. A literature search of PubMed, ISI, SCOPUS and Cochrane databases was conducted for relevant publications and their references, along with public documents, national and international guidelines, conference proceedings and presentations. From 5720 retrieved articles screened through title and abstract, 5346 were excluded and 374 assessed for full-text eligibility. For data extraction and quality assessment, 49 studies were included. Results of this review demonstrate that Radioactive Seed Localisation (RSL) and Radioactive Occult Lesion Localisation (ROLL) outperform Wire in terms of involved margins and reoperations. Between RSL and ROLL, there is a tendency to favour RSL. Similarly, Clip-guided localisation seems preferred when compared to ROLL, however further studies are needed. In summary, there seems to exist evidence that RSL and ROLL are better than Wire, representing potential alternatives, with a quick learning curve, better scheduling and management issues. Although, for recent techniques, more research is needed in order to achieve the same level of evidence. Highlights: The preoperative localisation of non-palpable lesions is an important and required procedure for breast conserving surgery. Each institution should adopt the most effective localization technique based on skills and technologies available. Both Radioactive Seed and Radioguided Occult Lesion Localization techniques seem to be potential alternatives to Wire.. Regarding other techniques, more studies are needed in order to achieve the same level of evidence.